Analisis Kesulitan Guru Kelas VII dalam Mengimplementasi Kurikulum Merdeka Belajar di SMP Negeri 5 Tulungagung - Yunita Sari; Nailariza Umami (Departement of Mathematics Education, 2024)
The independent curriculum is a learning curriculum that focuses on diverse intracurricular activities, with the hope that students can be more optimal and have enough time to strengthen competencies and deepen scientific concepts. At SMP Negeri 5 Tulungagung there are still teachers who experience difficulties in planning lessons in preparing administration such as analyzing learning outcomes and carrying out assessments. The researcher's aim in conducting this research was to determine the difficulties of class VII teachers in implementing the independent curriculum at SMP Negeri 5 Tulungagung. The type of research used was descriptive qualitative research with research informants, the principal, deputy head of curriculum, and 12 class VII subject teachers at SMP Negeri 5 Tulungagung. The techniques and instruments for collecting data for this research were carried out by means of interviews, observation and documentation. This research uses data analysis, namely data reduction, data presentation, drawing conclusions and verification. Based on the research results, it shows that there are several teachers experiencing difficulties in implementing the independent curriculum. The following are some of the difficulties faced by teachers, namely: teachers are not optimal in participating in independent curriculum training, teachers still experience administrative difficulties in analyzing learning outcomes and developing teaching modules that are adapted to school conditions and students, lack of complete IT-based learning media, such as LCD projectors which is not yet available in every class, there are some teachers who find it difficult to implement technology-based learning, and when it comes to entering grades into E-Reports, some teachers tend to have different understandings in determining minimum grades because there are no Minimum Completion Criteria.